Integrating High‐Resolution and Solid‐State Magic Angle Spinning NMR Spectroscopy and a Transcriptomic Analysis of Soybean Tissues in Response to Water Deficiency. Issue 6 (19th July 2017) - Coutinho, Isabel D.; Moraes, Tiago Bueno; Mertz‐Henning, Liliane Marcia; Nepomuceno, Alexandre Lima; Giordani, Willian; Marcolino‐Gomes, Juliana; Santagneli, Silvia; Colnago, Luiz Alberto
Abstract: Introduction: Solid‐state NMR (SSNMR) spectroscopy methods provide chemical environment and ultrastructural details that are not easily accessible by other non‐destructive, high‐resolution spectral techniques. High‐resolution magic angle spinning (HR‐MAS) has been widely used to obtain the metabolic profile of a heterogeneous sample, combining the resolution enhancement provided by MAS in SSNMR with the shimming and locking procedures in liquid‐state NMR. Objective: In this work, we explored the feasibility of using the HR‐MAS and SSNMR techniques to identify metabolic changes in soybean leaves subjected to water‐deficient conditions. Methodology: Control and water‐deficient soybean leaves were analysed using one‐dimensional (1D) HR‐MAS and SSNMR. Total RNA was extracted from the leaves for the transcriptomic analysis. Results: The 1 H HR‐MAS and CP‐MAS 13 C{ 1 H} spectra of soybean leaves grown with and without water deficiency stress revealed striking differences in metabolites. A total of 30 metabolites were identified, and the impact of water deficiency on the metabolite profile of soybean leaves was to induce amino acid synthesis. High expression levels of genes required for amino acid biosynthesis were highly correlated with the compounds identified by 1 H HR‐MAS. Conclusions: The integration of the 1 H HR‐MAS and SSNMR spectra with the transcriptomic data provided a complete picture of the major changes in the metabolic profile of soybeans in response to water deficiency. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : This study revealed the potential of integrating NMR‐MAS and transcriptomic data. The primary metabolites were up‐regulated by water deficiency and were properly assigned in the 1H HR‐MAS spectrum, rigid and semi‐rigid polysaccharides were readily observed using CP‐MAS and mobile components were observed by SPE‐MAS during the SSNMR analysis. In addition, multiple copies of the genes involved in the biosynthesis of the compounds affected by the water deficiency were identified in the soybean genome.